STUDI PERILAKU PERKECAMBAHAN BIJI DAN MORFOLOGI PERTUMBUHAN SEMAI KENANGA (Cananga odorata (Lam) Hook.f.et.Thomson) - Handayani, Tri (Buletin Kebun Raya, 2008)
Cananga (Cananga odorata) belongs to Annonaceae family. It is potentially used for many purposes, such as for ornamental plant, roadside tree, and timber tree, or as an important component in traditional medicines, traditional ceremonies and the production of some perfumes and biopesticides. As a part of promoting the species conservation and utilization, a study on seed germination of Cananga was carried out in the Bogor Botanic Gardens to observe the viability, germination characteristics and seedling morphology of seeds collected from the Bogor Botanic Gardens plant collection. As many as 450 mature seeds of Cananga were directly sown in three germination beds containing sand medium for germination capacity observation and the other 50 seeds were sown in a separate bed for germinant growth observation. It was noted that seedling emergence of Cananga started at 24 days after sowing and terminated at 45 days after sowing. The total seed germination was 58.05 %. Seedling emergence of Cananga odorata follows an epigeal pattern that shows the leafy emergent cotyledons.